Awareness, Attitudes and Perceptions of Medical Students Towards Refractive Surgery - Divya Trivedi; Deepti Mujumdar; Harpal Singh (TNOA Journal of Ophthalmic Science and Research)
Purpose: To assess undergraduate medical students’ understanding of refractive surgery. Materials and Methods: A cross-sectional questionnaire-based study was conducted among undergraduate medical students at a medical college in central India. Results: Of the 643 students who participated in the study, 596 (92.62%) were aware of the existence of surgical procedures for the correction of refractive errors. Three hundred and twenty-four (54.36%) of them felt vision could become poor again after refractive surgery, 383 (64.26%) said that refractive surgery is a painless procedure, 281 (47.14%) stated that refractive surgery does not leave a permanent scar on the eye, 327 (54.86%) believed that the ideal age to get refractive surgery done is between 20 and 30 years and 354 (59.39%) were of the opinion that eye drops need to be instilled for 3–6 months after surgery. One hundred and ninety-two (32.21%) knew that refractive surgeries can correct all three refractive errors, and 137 (40.29%) were willing to undergo the procedure themselves. The reasons cited by those reluctant to undergo surgical correction (59.70%) were inadequate information (32.01%), high cost of the procedure (24.13%) and fear of further loss of vision (20.19%). Doctors (55.53%) and social media (32.88%) were found to be the most common sources of information about refractive surgery. Conclusion: In spite of good awareness about refractive surgery among undergraduate medical students, they remain hesitant to undergo the procedure themselves. Doctors and social media platforms form the most common sources of information about these procedures.